Effect of Alloying Additions and Heat Treatment on the Microstructure Evolution of Nb─16Si Alloy. (2016) - Sankar, M.; Phanikumar, G.; Prasad, V.V.Satya
Abstract: In this study, the effect of Ta, Ni, Zr additions and heat treatment on the microstructure and hardness of Nb-16Si have been investigated. It was observed that Ta addition has not changed the microstructure of the alloy, while Ni and Zr additions drastically changed the microstructure of the alloys. The alloying additions increased the hardness of the alloys in as cast condition. However, hardness of phases present in the alloy decreased after heat treatment. Nbss and Nb3 Si phases were observed in Nb-16Si and Nb-16Si-3Ta alloys while Nbss and Nb5 Si3 phases were observed in Nb-16Si-3Ni and Nb-16Si-3Zr alloys after heat treatment.